Biosensor for direct bioelectrocatalysis detection of nitric oxide using nitric oxide reductase incorporated in carboxylated single-walled carbon nanotubes/lipidic 3 bilayer nanocomposite - Filipa O. Gomes (2019)
An enzymatic biosensor based on nitric oxide reductase (NOR; purified from Marinobacter hydrocarbonoclasticus) was developed for nitric oxide (NO) detection. The biosensor was prepared by deposition onto a pyrolytic graphite electrode (PGE) of a nanocomposite constituted by carboxylated single-walled carbon nanotubes (SWCNT5), a lipidic bilayer [1,2-di-(9Z-octadecenoy1)-sn-glycero-3-phosphoethanolamine (DOPE), 1,2-di-(9Z-octadecenoyl)-3-trimethylammonium-propane (DOTAP), 1,2-distearoyl-sn-glycero-3-phosphoethanolaminepolyethylene glycol (DSPE-PEG)] and NOR NOR direct electron transfer and NO bioelectrocatalysis were characterized by several electrochemical techniques. The biosensor development was also followed by scanning electron microscopy and Fourier transform infrared spectroscopy. Improved enzyme stability and electron transfer (1.96 x 10(-4) cm.s(-1) apparent rate constant) was obtained with the optimum SWCNTs/(DOPE:DOTAP:DSPEPEG)/NOR) ratio of 4/2.5/4 (v/v/v), which biomimicked the NOR environment. The PGE/ISWCNTs/(DOPE: DOTAP:DSPE-PEG)/NOR] biosensor exhibited a low Michaelis-Menten constant (4.3 uM), wide linear range (0.44-9.09 mu M), low detection limit (0.13 mu M), high repeatability (4.1% RSD), reproducibility (7.0% RSD), and stability (ca. 5 weeks). Selectivity tests towards L-arginine, ascorbic acid, sodium nitrate, sodium nitrite and glucose showed that these compounds did not significantly interfere in NO biosensing (91.0 +/- 93%-98.4 +/- 53% recoveries). The proposed biosensor, by incorporating the benefits of biomimetic features of the phospholipid bilayer with SWCNT's inherent properties and NOR bioelectrocatalytic activity and selectivity, is a promising tool for NO.